Kampanye “Saring Sebelum Sharing” sebagai Upaya Penguatan Literasi Digital Muslimah Aisyiyah di Palu Barat - Mochammad Muchlis Romadon; Novita Salwa; Fachri Kurnia Bhakti B; Mardiah Mardiah; Munarif Munarif (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2025)
The rapid development of digital technology has transformed patterns of communication and information dissemination within society, including religious communities. While digital media facilitate easy access to information, they also increase the spread of misinformation, disinformation, and hoaxes. This condition highlights the urgent need to strengthen digital literacy and information ethics so that communities can manage information critically and responsibly. This article aims to describe the implementation and impact of a community service program focused on strengthening digital literacy and information ethics among Muslimah Aisyiyah study groups in Palu Barat District through the Saring Sebelum Sharing campaign. The program employed the Participatory Learning and Action (PLA) approach, positioning participants as active subjects in the learning process through educational, dialogical, and hands-on activities. The program was conducted through several sessions, including raising awareness of the urgency of digital literacy, identifying linguistic characteristics of hoaxes, reinforcing information ethics from an Islamic perspective through the principle of tabayyun, and providing training in information verification and the identification of artificial intelligence–based manipulation. The results indicate a significant improvement in participants’ knowledge, attitudes, and skills in filtering, evaluating, and sharing digital information wisely. This program demonstrates that a participatory approach integrated with Islamic values is effective in fostering a culture of critical, ethical, and responsible digital literacy.ABSTRAKPerkembangan teknologi digital telah mengubah pola komunikasi dan penyebaran informasi di masyarakat, termasuk dalam komunitas keagamaan. Kemudahan akses informasi melalui media sosial dan aplikasi pesan instan turut meningkatkan risiko penyebaran misinformasi, disinformasi, dan hoaks. Kondisi ini menuntut penguatan literasi digital dan etika informasi agar masyarakat mampu mengelola informasi secara kritis dan bertanggung jawab. Artikel ini bertujuan mendeskripsikan pelaksanaan dan dampak program pengabdian masyarakat berupa penguatan literasi digital dan etika informasi bagi Muslimah Pengajian Aisyiyah di Kecamatan Palu Barat melalui kampanye Saring Sebelum Sharing. Metode yang digunakan adalah Participatory Learning and Action (PLA) yang menempatkan peserta sebagai subjek aktif dalam proses pembelajaran melalui kegiatan edukatif, dialogis, dan praktik langsung. Program dilaksanakan melalui beberapa sesi, meliputi peningkatan kesadaran urgensi literasi digital, pengenalan ciri kebahasaan hoaks, penguatan etika informasi dalam perspektif Islam melalui prinsip tabayyun, serta pelatihan verifikasi informasi dan pengenalan manipulasi berbasis kecerdasan buatan. Hasil kegiatan menunjukkan peningkatan signifikan pada pengetahuan, sikap, dan keterampilan peserta dalam menyaring, mengevaluasi, dan menyebarkan informasi digital secara bijak. Program ini membuktikan bahwa pendekatan partisipatif yang terintegrasi dengan nilai-nilai keislaman efektif dalam membangun budaya literasi digital yang kritis, etis, dan bertanggung jawab.